Linifanib – a multi-targeted receptor tyrosine kinase inhibitor and a low molecular weight gelator - Marlow, Maria; Al-Ameedee, Mohammed; Smith, Thomas; Wheeler, Simon; Stocks, Michael J. (Royal Society of Chemistry, 2015)
In this study we demonstrate that linifanib, a multi-targeted receptor tyrosine kinase inhibitor, with a key urea containing pharmacophore, self-assembles into a hydrogel in the presence of low amounts of solvent. We demonstrate the role of the urea functional group and that of fluorine substitution on the adjacent aromatic ring in promoting self-assembly. We have also shown that linifanib has superior mechanical strength to two structurally related analogues and hence increased potential for localisation at an injection site for drug delivery applications.